Renewable Poly(Thioether‐Ester)s from Fatty Acid Derivatives via Thiol‐Ene Photopolymerization. (11th June 2019) - Moser, Bryan R.; Doll, Kenneth M.; Peterson, Steven C.
Abstract: Partially bio‐based poly(thioether‐ester)s were obtained in high conversion from thiol‐ene photopolymerization of fatty dienes with dithiols utilizing mild, solventless reaction conditions. Fatty dienes were synthesized by esterification of 9‐decenoic acid, a terminally unsaturated medium‐chain fatty acid that can be obtained from ethenolysis of oleic acid, with ethylene glycol and 9‐decen‐1‐ol to yield bio‐based dienoic monomers amenable to subsequent thiol‐ene polymerization. Polycondensation with 1, 2‐ethanedithiol (EDT) and 1, 3‐propanedithiol (PDT) gave a series of semicrystalline poly(thioether‐ester)s with degrees of polymerization that ranged from 29 to 85, polydispersity indices between 2.81 and 4.38, and glass transitions from −36.8 to −25.7 °C. The polymers were elastic at room temperature, with EDT‐linked materials exhibiting greater elasticity than the corresponding PDT‐linked polymers. All polymers were thermally stable below 320 °C, with 10% mass loss ( T 10 ) occurring above 338 °C. Enthalpies of fusion increased with higher relative crystallinity and were greater than the corresponding enthalpies of crystallization. The polymers were soluble in nonpolar solvents such as chloroform and THF but resisted dissolution in more polar solvents with dielectric constants above 10. Furthermore, the polymers were susceptible to acidic hydrolysis but resisted basic hydrolysis at room temperature.